Il paliotto d’argento di Olimpia Aldobrandini su disegno di Carlo Fontana nella Chiesa del Gesù di Roma.: Dalla prima apparizione documentaria alla dispersione (1682-1798) - Marangon, Elisa (Eikón / Imago, 2025)
Since the early 1980s, research on the figure and functions of agents in Early modern Europe offered the possibility for an ever-increasing number of scholars to approach the topic using several interpretative models and approaches. In particular, the analysis of political, social, and artistic networks based on epistolary sources has proven to be the favoured method of investigation by scholars: the correspondence of the prince-bishop of Olomouc Karl von Lichtenstein-Castelcorno with the members of the Roman Curia is no exception. The role of intermediary between the Roman environment and the bishop was played by his agent Giovanni Petignier. In a letter sent in August 1682, Petignier informed his patron about the donation of a six-hundred-pound silver antependium to the Church of Gesù by Princess Olimpia Aldobrandini-Pamphilj. The purpose of this article concerns the historical reconstruction of the events that led to the loss of the piece of furniture, as well as underlying the role played by the bishop’s agent as cultural transfer with the Roman cultural context during the late seventeenth century. Finally, the attribution of the sculpture to Ticino architect Carlo Fontana will be analysed as well by investigating his connections with the Pamphilj family.